Helicobacter pylori infection induces DNA double-strand breaks through the ACVR1/IRF3/POLD1 signaling axis to drive gastric tumorigenesis - Xinbo Xu; Xiao Fei; Huan Wang; Xidong Wu; Yuan Zhan; Xin Li; Yan’an Zhou; Chunxi Shu; Cong He; Yi Hu; Jianping Liu; Nonghua Lv; et al. (Gut Microbes)
Helicobacter pylori (H. pylori) infection plays a pivotal role in gastric carcinogenesis through inflammation-related mechanisms. Activin A receptor type I (ACVR1), known for encoding the type I receptor for bone morphogenetic proteins (BMPs), has been identified as a cancer diver gene across various tumors. However, the specific role of AVCR1 in H. pylori-induced gastric tumorigenesis remains incompletely understood. We conducted a comprehensive analysis of the clinical relevance of ACVR1 by integrating data from public databases and our local collection of human gastric tissues. In vitro cell cultures, patient-derived gastric organoids, and transgenic INS-GAS mouse models were used for Western blot, qRT-PCR, immunofluorescence, immunohistochemistry, luciferase assays, ChIP, and comet assays. Furthermore, to investigate the therapeutic potential, we utilized the ACVR1 inhibitor DM3189 in our in vivo studies. H. pylori infection led to increased expression of ACVR1 in gastric epithelial cells, gastric organoid and gastric mucosa of INS-GAS mice. ACVR1 activation led to DNA double-strand break (DSB) accumulation by inhibiting POLD1, a crucial DNA repair enzyme. The activation of POLD1 was facilitated by the transcription factor IRF3, with identified binding sites. Additionally, treatment with the ACVR1 inhibitor DM3189 significantly ameliorated H. pylori-induced gastric pathology and reduced DNA damage in INS-GAS mice. Immunohistochemistry analysis showed elevated levels of ACVR1 in H. pylori-positive gastritis tissues, showing a negative correlation with POLD1 expression. This study uncovers a novel signaling axis of AVCR1/IRF3/POLD1 in the pathogenesis of H. pylori infection. The upregulation of ACVR1 and the suppression of POLD1 upon H. pylori infection establish a connection between the infection, genomic instability, and the development of gastric carcinogenesis.